Sistem Kontrol Teleskop Ioptron AZ Mount Pro Berbasis Android - Taufikurrahman, Arief (Universitas Islam Negeri Mataram, 2022)
The development of astronomical observation instrument technology makes astronomical observations easier and simpler. One of them is a telescope equipped with a computerized motor. Control of the telescope can now be done wirelessly through an android application on a smartphone, one of which is the Sky Safari Plus 6 application. By using the Ioptron AZ Mount Pro telescope, the telescope can be controlled using the Sky Safari Plus 6 application wirelessly via a smartphone without using a computer and additional driver.